Implementation of Pancasila Values in Daily Life Through Civics Subjects for Elementary School Students - Resti Novia Rahayu; Farida Catur Wahyu Anggriyani (Penerbit Hellow Pustaka, 2025)
Pancasila, as the foundation of the Indonesian state and the worldview of the Indonesian people, contains values that are important to be applied in daily life. One of the efforts to instill the values of Pancasila in the younger generation is through the subject of Civics Education (PKn) in elementary schools. This article aims to examine the implementation of Pancasila values in daily life among elementary school students through PKn learning. The approach used in this research is library research, by collecting and analyzing various literature sources related to the application of Pancasila in education. The research findings show that the PKn subject plays an important role in instilling Pancasila values, such as mutual cooperation, social justice, and respect for diversity, which can be applied in students' daily lives. This implementation also requires support from the family and community environment to achieve optimal success.